2019
DOI: 10.3168/jds.2018-15524
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein fractions strongly affect the patterns of coagulation, curd firming, and syneresis

Abstract: The aim of this study was to assess the role of milk protein fractions in the coagulation, curd firming, and syneresis of bovine milk. Analyses were performed on 1,271 individual milk samples from Brown Swiss cows reared in 85 herds classified into 4 types of farming systems, from the very traditional (tied cows, feed manually distributed, summer highland pasture) to the most modern (loose cows, use of total mixed rations with or without silage). Fractions α S1 -casein (CN), α S2 -CN, β-CN, κ-CN, β-lactoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 34 publications
5
36
0
7
Order By: Relevance
“…Among the whey protein fractions, we found β-LG in amounts approximately 3.5 times that of α-LA. This result is in agreement with data from previous studies [9,19,20].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Among the whey protein fractions, we found β-LG in amounts approximately 3.5 times that of α-LA. This result is in agreement with data from previous studies [9,19,20].…”
Section: Discussionsupporting
confidence: 94%
“…Heck et al [21] and Bobe et al [23] observed that β-LG variants affected determination of its proportion in milk, and also affected β-CN and k-CN proportions of the total milk protein. These correlations indicate that selection for lower proportions of β-LG should increase the proportion of k-CN in milk, with positive effects on milk coagulation [18,20,32]. Highly significant interactions between β-CN, κ-CN and β-LG have been reported in literature which could be explained by the existence of epistatic effects between the genes coding for these proteins [33].…”
Section: Genetic and Phenotypic Correlationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Yield can be predicted by applying specific formulae that have been developed by several researchers: originally, they were only based on total protein and fat content of milk, but other parameters were included with time. In particular, it has been demonstrated that the casein polymorphism connected to genotype, season, stage of lactation, and parity of the cows also make an important contribution [ 6 , 7 , 8 , 9 , 10 ]. The matter is under continuous investigation, and some physical aspects, such as the size of casein micelles and of milk fat globules, have been considered.…”
Section: Technological Properties Of Milkmentioning
confidence: 99%
“…With regard to coagulation properties of goat milk, Stocco et al (2018b) reported that high values of casein number (>82%) were associated with a general improvement of coagulation ability of goat milk, but no information is available about the effect of casein number on milk nutrient recovery in goat cheese. Some studies on bovine milk have clarified that, other than the ratio between caseins and whey proteins, the proportions among individual caseins and whey protein fractions also significantly affect both milk coagulation properties (Amalfitano et al, 2019) and cheesemaking efficiency traits (Cipolat-Gotet et al, 2018). Large breed differences in the proportions among individual protein fractions in goat milk have been demonstrated (Moatsou et al, 2008;Thomann et al, 2008), but their effects were only studied in relation to milk coagulation properties (Clark and Sherbon, 2000) and cheese yield (Damián et al, 2008).…”
Section: Contribution Of Casein Numbermentioning
confidence: 99%